Relationship between Leadership styles of Physical Education Department Managers with Sports Volunteers' Satisfaction - Farogh Fathi Kajal; Mehrali Hemmatinezhad; Seyed Mohammad Hossein Razavi (The Society of Aging and Physical Activity (SAPA), 2013)
This study aims to survey the relationship between leadership styles of physical education (P.E) department managers with sports volunteers' satisfaction. 173 of all heads of sport boards of Ardabil Province which were in active level (N = 180) responses to multi-factor leadership questionnaire (MLQ) and the volunteers' experiences were used for satisfaction data. Reliability of the questionnaire (Cronbach's alpha) was α = 0.86 and α=0.92, respectively. Transformational leadership style, and pragmatic style have a positive (r=0.407 and r=0.253 respectively) and significant (P=0.001) relationship with volunteers' satisfaction and there is a negative and significant relationship between inefficacious leadership style and volunteers' satisfaction (r=-0.389, P=0.001). Also, there were significant differences between priorities of leadership styles of P.E department managers; transformational (3.914±0.617), pragmatic (3.471±0.607), and inefficacious (2.094±1.057) styles were respectively at the first, second, and third priority. In terms of volunteers, social satisfaction, job satisfaction, and experience were the most important and material satisfaction was the least important dimensions. According to the results of this study, it seems that managers of physical education departments can use transformational and inspirational leadership styles for directing the volunteers in sport boards.